Deep eutectic-solvothermal synthesis of nanostructured Fe3S4 for electrochemical N2 fixation under ambient conditions. Issue 92 (5th November 2018) - Zhao, Xinhui; Lan, Xue; Yu, Dongkun; Fu, Hui; Liu, Zhimin; Mu, Tiancheng
Abstract : One-step solvothermal synthesis of metal sulfides by combining solvothermal synthesis and sulfuration processes. These sulfides show a high catalytic efficiency for nitrogen reduction reactions. Abstract : We report the synthesis of nanostructured Fe3 S4 from deep eutectic solvents via a one-step solvothermal method. The as-obtained Fe3 S4 catalyst was capable of electrochemically reducing N2 to NH3 under ambient conditions, and exhibits a high NH3 yield (75.4 μg h −1 mg −1 cat. ) and faradaic efficiency (6.45%) at −0.4 V vs. a reversible hydrogen electrode.